Role of Fine Needle Aspiration Cytology in Extrapulmonary Tuberculosis - Acharya, Subarna; Gupta, Sharmila (Journal of Nepalgunj Medical College, 2021)
Introduction: Extrapulmonary tuberculosis is equally important as that of pulmonary tuberculosis. Fine needle aspiration cytology (FNAC) is accurate, cost effective, minimal invasive outpatient procedure and aids in prompt diagnosis of extrapulmonary tuberculosis. Aims: To determine the role of fine needle aspiration cytology for diagnosis of extra pulmonary tuberculosis. Methods: This is a hospital based descriptive study done over a period of one and half year April 2019 to October 2020 at Nepalgunj Medical College Teaching Hospital, Nepalgunj, Nepal. All the 80 patients who were clinically suspected for tuberculosis had undergone fine needle aspiration cytology and diagnosed as tuberculosis in cytology were included in study. Cytological diagnosis was made with microscopic features and positive acid fast bacilli staining. Microscopy showed epithelioid histiocytes, granulomas, multinucleated giant cells, caseous necrosis, neutrophils and mature lymphocytes. Results: Out of 930 cases received, 80 cases were diagnosed as tuberculosis in cytology. 33 cases were diagnosed with acid fast bacilli positive. Rest was diagnosed with cytological features. Among 80 aspirated samples, a portion of purulent specimen was evaluated with Genexpert test in 11 cases for Mycobacterium Tuberculosis detection and rifampicin sensitivity/ resistant. Out of 11 positive patients in Genexpert tests; 10 were rifampicin sensitive and one was rifampicin resistant. Conclusion: Common presentation of extrapulmonary tuberculosis is in lymph nodes with increased frequency in age group of 21 to 30 years. Therefore, lymph nodes in this age group should be prioritized more for investigation of extrapulmonary tuberculosis.